Harmonizing the religion, arts, and culture: Value of compassion as a conflict resolver in Sumedang - Hilman Taufiq Abdillah; Syahidin Syahidin (Dedicated: Journal of Community Services (Pengabdian kepada Masyarakat), 2025)
Sumedang Regency faces a sociological challenge in the form of a sharp dichotomy between puritanical religious practices and local cultural arts expressions. This phenomenon hinders the optimization of social capital in building community character. This article aims to deconstruct the roots of this dichotomous conflict and reconstruct a new synergy model based on the Grand Theory of the integration of religion, arts, and culture, with the value of "compassion" (Ar-Rahman Ar-Rahim/Silih Asih) as an axiological meeting point. Data were collected through participant observation, in-depth interviews with seven key informants (clerics, artists, academics, bureaucrats), and extensive literature reviews conducted through Community Service (Pengabdian kepada Masyarakat or PkM) activities. The results show that the dichotomy arises from a paradigmatic misunderstanding of religion, which is understood solely as a formalistic ritual. At the same time, arts and culture are considered profane and distant from God. The main findings demonstrate that compassion can serve as an epistemological bridge, with religion providing the ethical foundation, culture providing a communal symbolic container, and art serving as an expressive medium of divine beauty (Jamal). The synergy of these three dimensions creates strong social cohesion and an inclusive character education model in Sumedang.   Abstrak Kabupaten Sumedang menghadapi tantangan sosiologis berupa dikotomi tajam antara praktik keagamaan yang puritan dan ekspresi seni budaya lokal. Fenomena ini menghambat optimalisasi modal sosial dalam pembangunan karakter masyarakat. Artikel ini bertujuan untuk mendekonstruksi akar konflik dikotomis tersebut dan merekonstruksi model sinergi baru menggunakan Grand Theory integrasi agama, seni, dan budaya dengan nilai "kasih sayang" (Ar-Rahman Ar-Rahim/Silih Asih) sebagai titik temu (meeting point) aksiologis. Pengumpulan data dilakukan dengan observasi partisipatif, wawancara mendalam terhadap tujuh informan kunci (ulama, seniman, akademisi, birokrat), dan studi literatur ekstensif melalui kegiatan Pengabdian kepada Masyarakat (PkM). Hasil menunjukkan bahwa dikotomi terjadi akibat misunderstanding paradigmatik terhadap agama yang dipahami sebatas ritual formalistik, sementara seni budaya dianggap profan dan menjauhkan dari Tuhan. Temuan utama membuktikan bahwa nilai kasih sayang mampu menjadi jembatan epistemologis di mana agama menyediakan landasan etika kasih sayang, budaya menyediakan wadah simbolik komunal, dan seni menjadi media ekspresif keindahan ilahiah (Jamal). Sinergi ketiga dimensi ini menciptakan kohesi sosial yang kuat dan model pendidikan karakter yang inklusif di Sumedang. Kata Kunci: agama; budaya; nilai kasih sayang; resolusi konflik; seni ekspresif